2021
DOI: 10.1037/dev0001256
|View full text |Cite
|
Sign up to set email alerts
|

Family context in association with the development of child sensory processing sensitivity.

Abstract: Informed by the biological sensitivity to the context (BSC) theory, this multimethod, longitudinal study sought to examine how family context may be associated with the development of child sensory processing sensitivity (SPS) over a year. Participants were 235 young children (M age = 2.97 at the first measurement occasion, 55.3% were girls) and their parents (median annual household income: $55,000 to 74,999), who were followed for two annual measurement occasions. These children consisted of 56.2% White, 21.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…Firstly, based on the ICCs (Supplementary Table S8), self-reported sensitivity evinced proportionally more within-person than between-person (0.09) variance, suggesting lower trait stability over one year than has been previously documented [83]. Importantly, the stability of sensitivity in children appears to fluctuate in relation to the harshness of the environment [83] -an effect possibly complicated by the unpredictable refugee contextmaking it notably more challenging to identify stable associations. In future analyses, possible causes underpinning this high withinperson variability should be investigated.…”
Section: Discussionmentioning
confidence: 91%
“…Firstly, based on the ICCs (Supplementary Table S8), self-reported sensitivity evinced proportionally more within-person than between-person (0.09) variance, suggesting lower trait stability over one year than has been previously documented [83]. Importantly, the stability of sensitivity in children appears to fluctuate in relation to the harshness of the environment [83] -an effect possibly complicated by the unpredictable refugee contextmaking it notably more challenging to identify stable associations. In future analyses, possible causes underpinning this high withinperson variability should be investigated.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, increased ES in adults predicts greater levels of anxiety and depression and lower life satisfaction in the context of poor nurturing environments and unfavourable childhood experiences (Booth et al, 2015;Liss et al, 2005) and empirical studies also showed that highly sensitive adults are more impacted by the exposure to negative media pictures (Rubaltelli et al, 2018). On the other hand, highly sensitive children benefit more from positive parenting , Li et al, 2021, and highly sensitive preadolescents and adolescents exceptionally benefit from psychological prevention programs (Ceccon et al, 2023;de Villiers et al, 2018;Nocentini et al, 2018;Pluess & Belsky, 2013;Pluess and Boniwell, 2015;Pluess et al, 2017). Similarly, highly sensitive employees are more responsive to positive job characteristics in terms of positive job attitudes (Vieregge et al, 2023).…”
Section: Environmental Sensitivity For Better and For Worsementioning
confidence: 99%
“…The stability of sensitivity across development has not been investigated in depth yet. Intriguingly, first evidence suggests that observer-rated sensitivity in three year old children can change within a year as a function of environmental quality [ 135 ], a result not inconsistent with Biological Sensitivity to Context thinking. Future studies should investigate to what degree prenatally programmed sensitivity is stable across subsequent developmental periods and identify the postnatal exposures that are likely to reverse or modify prenatally programmed environmental sensitivity.…”
Section: Unknowns In the Prenatal Programming Equationmentioning
confidence: 99%